Exploring the association between personality traits and leadership: A systematic literature review - Noradilah, Md Nordin; Nor Aishah, Othman; Mansor, Abu Talib (Malque Publishing, 2025)
Understanding personality-related factors that influencing leadership is crucial for guiding stakeholders toward achieving long-term organizational goals, as leadership effectiveness is demonstrably shaped by individual dispositions impacting decision-making, interpersonal dynamics, and motivation. Although the association between personality traits and leadership has been extensively examined across diverse contexts, systematic reviews synthesizing recent empirical evidence remain relatively insufficient. Therefore, this study aims to systematically explore how diverse personality frameworks relate to leadership outcomes by reviewing literature published between 2019 and 2024. Utilizing predefined inclusion and exclusion criteria, a systematic review identified, selected, and rigorously analyzed 22 peer-reviewed articles sourced from Scopus, Web of Science, and Google Scholar databases. The findings consistently reveal significant associations between all five Big Five traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) and leadership, with extraversion exhibiting a strong positive correlation and neuroticism demonstrating a prominent negative correlation. Furthermore, traits from alternative models, specifically honesty-humility from the HEXACO framework and enterprising characteristics from the RIASEC model, were also identified as positive contributors to leadership development. These results emphasize the critical importance of integrating insights from multiple personality theories to gain a more detailed and comprehensive understanding of leadership functioning across different organizational and cultural settings. Beyond its theoretical implications, this review offers valuable, evidence-based insights for educators designing leadership syllabuses, organizational consultants developing talent management programs, and policymakers formulating strategies to cultivate leadership pathways. By identifying robust and consistent personality predictors of leadership, this study contributes meaningfully to the expanding literature focused on enhancing leadership capacity at individual and organizational levels, thereby supporting more effective and sustainable goal achievement.